Online Learning Using Google Incorporated for Student High School: Mapping Motivation Using Rasch Model in Physics Learning - Moh. Irma Sukarelawan; Ariati Dina Puspitasari; Zulfa 'Amalia Rahmatika; Dennis Dennis; Ishafit Ishafit; Fitri Nur Hikmah; Toni Kus Indratno; Eko Nur Sulistyo (Berkala Ilmiah Pendidikan Fisika, 2022)
This study aimed to determine the motivation level of high school students during online learning using Google Incorporated. This research is included in the type of survey research. The survey was conducted in one high school in the city of Yogyakarta. Respondents consisted of 32 people (L = 46% and P = 54%) students of class X. Student motivation was evaluated using a motivational instrument consisting of 14 items and spread over three aspects: motivation, self-efficacy, and responsibility. The instrument uses a 5-point Likert scale, from Strongly Disagree (1) to Strongly Agree (5). The level of student motivation was analyzed using the Rasch model with the Logit Value of Person (LVP) technique combined with the Wright map and Differential Item Functioning (DIF). The analysis results show that 41% of students have a moderate level of motivation, 25% at a high level, 19% at a very high level, and 16% at a low level. The results of the DIF analysis show that one of the items (Re4) in the Responsibility aspect tends to benefit female students. This has implications for the emergence of student interest in studying physics.